Family therapy in primary health care. - Magalhães, Cristina (2001)
The growing number of problems out of the scope of general practice that GPs at the Sete Rios Health Centre have to deal with on a daily basis, led a group of the former to ask the Health Centres Director in 1997 for specific support in family therapy services. This new project was thus set up in January 1998 in order to help dysfunctional families to change towards more effective and satisfactory ways of functioning by their members. This project also aimed to foster a systemic understanding of this type of problems by the health centres professionals. Family therapists and family doctors started to articulate and meet periodically to discuss cases. With 4-hour weekly sessions, the project included 52 families on therapy with which 212 systemic family interviews were conducted. Reasons for referral for therapy were studied, and a systemic diagnostic assessment of the cases was made. Among the families that complied with the therapeutic process, there was a decrease in the number of GP surgery visits. Furthermore, there was a decrease or even resolution of symptoms in 53% of the cases for which the therapeutic process was deemed complete - either on account of discharge, referral or drop-out.